Malaysian legal framework on limitation of artistic expression: an analysis of the film industry / Nadia Nabila Haji Mohd Saufi … [et al.] - Mohd Saufi (Haji), Nadia Nabila; Mohd Azmi Lwin, Mohamad Afiq; Mohd Yusof, Mohd Yusizwan; Suratman, Nor Azman (2011)
In Malaysian entertainment industry, there are many factors that could hinder certain production of art work. The government plays an important role to facilitate all growth and back lashes from within Malaysian entertainment industry. Among the issues frequently arise in film industry is on controversial issues such as disagreements on social and political views, issues of sensitivity, perception of double-standards and also profit generation from film industry. The relevant law that governs issues as above is Censorship Act 1952, Sedition Act 1948. One hundred percent freedom in art creations are given to the industry players (directors, producers, etc) however, government impose outlines to comply with regarding mass production to general public. The late Yasmin Ahmad have issues pertaining and involving Censorship Act in her film Sepet, though her film is appreciated as well as criticized by many, restrictions are still imposed towards her. On the contrary, Name Wee is let off or waived though his "art work" is disliked by many Malaysian. Quality of film industry in Malaysia is cautioned to be not of expected quality. In short, it is concern that by editing or screening done by the government would affect the art work. This qualitative study is to critically analyze the gap that has been conducted in previous studies and to roughly or merely grasp whether or not subsequent result from rules imposed by the government give positive and negative outcome to art production. "Gaps" are problems as to how directors and composers comply with the rules and regulations imposed on them. Art work symbolizes national identity.